Conversion of a company and the act on shaping the agricultural system - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2019)
The Act of 11 April 2003 on shaping the agricultural system introduced a number of restrictions on trading in agricultural property. As of 30 April 2016, the regulations of the Act also apply to companies undergoing a division, change of status or a merger. In this article a change of status of a company which owns agricultural real estate was analysed. For practical reasons, the most common situation of this kind is the conversion of a limited liability company into a public limited company. The analysis of this has revealed that the construction of legal regulations regulating this issue is highly imprecise. However, the biggest problem seems to be the fact that statutory objectives provided for in the Act have not been achieved. In the case of a conversion of a limited liability company into a public limited company, the shareholders of the limited liability company become shareholders of the public limited company, so from the substantive law point of view, the same entity continues to exist. Solutions of this kind do not make any legal sense and certainly do not achieve any of the objectives set out in the Act analysed.